PENDIDIKAN BERBASIS GENDER AWARENESS ; STRATEGI MEMINIMALISIR BIAS GENDER DI PONDOK PESANTREN - Warliah, Wiwin (JURNAL ISLAM NUSANTARA, 2017)
This paper presents the strategy of pesantren Nurul Jadid Paiton Probolinggo in minimizing the occurrence of bias gender through gender-based education awareness.Bias gender in education is a reality that occurs in educational systems that favor certain sexes that cause gender inequality, so it takes a serious effort to overcome it, that is through gender awareness education. This research used qualitative approach of phenomenology type with one site design. The results showed; The form of bias gender in the system at Pesantren Nurul Jadid Paiton Probolinggo namely; the observed book content tend to be less gender-sensitive, the gap is due to structural factors such as socio-cultural values, and economics, the low participation of women in the educational decision making process and patriarchal culture. Development of gender-based education awareness at Nurul Jadid Paiton Probolinggo is done through; the establishment of the Association of Women Nurul Jadid Foundation, the treatment and giving equal opportunity to women in every educational activity, the women helped build quality families, women also have the obligation to practice religious practices through education activities and giving independence to women.